ENHANCING THE MECHANISMS AND FACTORS OF IMPROVING THE LITERACY OF UPPER SCHOOL STUDENTS BASED ON AN INNOVATIVE APPROACH - Yusupjanovna, Sobirova Makhbuba; Anvarjonovna, Isakova Gulzoda (Journal of Higher Education and Academic Advancement, 2024)
The given article presents information about the Uzbek language, the implementation of the law “On the State Language”, shortcomings in this regard, literacy issues, improving students’ literacy, research conducted in this regard, the role of the family in increasing students’ literacy. The impact of literacy, future challenges related to quality mother tongue instruction, increased attention to the issue of literacy, as well as issues related to the preparation of highly qualified personnel in this field will be covered. In the course of our research, we have found out that students have insufficient skills and qualifications to distinguish language phenomena, to choose words suitable for the purpose of speech. It is explained that the cultural level and responsibilities of parents are important in developing the student's spirituality, increasing the level of knowledge and literacy. Today, it will be shown what the tasks related to the development of our native language and literature, its teaching should consist of. Updating the system of teaching the Uzbek language on the basis of our national pedagogy, on the basis of foreign experience, creating literature that meets the requirements of the time, using innovative technologies, ensuring that the Uzbek language occupies a worthy place in the Internet world information network, about the language the need to create scientific and methodological developments related to the creation of electronic systematization of knowledge and linguistic analysis algorithms, the introduction of information and communication technologies to linguistic research, the importance of the creation of translation programs and dictionaries, electronic textbooks based on the Uzbek language and the world's leading foreign languages are stressed.